Schumpeterian aspects of growth and its correlative classical and neoclassical approaches - Berumen, Sergio A.; Llamazares, Francisco (Papeles de Europa, 2015)
Economic growth is a central concept in economic theory. Modern societies regard growth as an important determinant for rising standards of living. These effects can be observed not only in more goods and services but also in brand new products and processes. Investment in human capital is regarded as the very source of long-term, sustainable economic growth. The purpose of this article is to provide a brief description of economic growth, how to approach its measurement, and to provide a brief review of the Schumpeterian thought and the main schools that have undertaken its analysis.